(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is one of today’s current problems, it examines the fact that living a physically healthy life is the essence of a person’s life, the idea of healthy upbringing, and the issues of a healthy lifestyle of forming positive qualities and qualities of a person are highlighted.